The dream of Christian Nagasaki: world trade and the clash of cultures, 1560-1640 - Hesselink, Reinier H. (McFarland & Company, Inc. , Publishers, 2016)
"Nagasaki, on the west coast of the Japanese island of Kyushu, is known for having been the target of an atomic bomb attack on August 9, 1945. This book is the first comprehensive history of the rise and fall of Christian Nagasaki (1560-1640). The author provides narrative of the city's early years from European and Japanese perspective"